To solve for w, you can follow these steps:
1. Distribute the 2 to both terms inside the parentheses:
4w + 14 = 42
2. Subtract 14 from both sides of the equation to isolate the term with w:
4w = 28
3. Divide both sides of the equation by 4 to solve for w:
w = 28/4
4. Simplify the right side of the equation:
w = 7
Therefore, the solution to the equation 2(2w + 7) = 42 is w = 7.
solve for w
2(2w + 7) = 42
5 answers
solve for u
(4u - 6) = 36
(4u - 6) = 36
To solve for u, you can follow these steps:
1. First, add 6 to both sides of the equation to isolate the term with u:
4u - 6 + 6 = 36 + 6
Simplifying, we get:
4u = 42
2. Next, divide both sides of the equation by 4 to solve for u:
4u/4 = 42/4
Simplifying, we get:
u = 10.5
Therefore, the solution to the equation (4u - 6) = 36 is u = 10.5.
1. First, add 6 to both sides of the equation to isolate the term with u:
4u - 6 + 6 = 36 + 6
Simplifying, we get:
4u = 42
2. Next, divide both sides of the equation by 4 to solve for u:
4u/4 = 42/4
Simplifying, we get:
u = 10.5
Therefore, the solution to the equation (4u - 6) = 36 is u = 10.5.
solve for u
2(4u - 6) = 36
2(4u - 6) = 36
To solve for u, you can follow these steps:
1. Distribute the 2 to both terms inside the parentheses:
8u - 12 = 36
2. Add 12 to both sides of the equation to isolate the term with u:
8u - 12 + 12 = 36 + 12
Simplifying, we get:
8u = 48
3. Next, divide both sides of the equation by 8 to solve for u:
8u/8 = 48/8
Simplifying, we get:
u = 6
Therefore, the solution to the equation 2(4u - 6) = 36 is u = 6.
1. Distribute the 2 to both terms inside the parentheses:
8u - 12 = 36
2. Add 12 to both sides of the equation to isolate the term with u:
8u - 12 + 12 = 36 + 12
Simplifying, we get:
8u = 48
3. Next, divide both sides of the equation by 8 to solve for u:
8u/8 = 48/8
Simplifying, we get:
u = 6
Therefore, the solution to the equation 2(4u - 6) = 36 is u = 6.